Development of the Hypovolemic Shock Response Kit (Emergency Kit Containing Infusion Fluids and Pressure Dressing Equipment) at SMK Bina Banua Banjarmasin - M. Sobirin Mohtar; Ahmad Syahlani; Maria Fransiska Katni; Muhammad Ramadhani; Mitra Olivia; Mahdiyanti Mahdiyanti; Nurul Qamaril Wardani; Nasyuha Shirin Ebadi R; Nazilatul Audah Surya P; Nadila Nadila; Patmawati Patmawati; Rahmadana Rahmadana (Journal of Applied Community Service and Innovation, 2025)
Hypovolemic shock is a medical emergency condition that can be life-threatening due to significant loss of fluids or blood, leading to tissue hypoperfusion and organ failure. In Indonesia, the incidence of hypovolemic shock, particularly from trauma, dehydration, and bleeding, remains high. Therefore, prompt and appropriate intervention is crucial, especially among school students. This article aims to develop and introduce the Hypovolemic Shock Response Kit (an emergency kit containing infusion fluids and pressure dressing equipment) at SMK Bina Banua Banjarmasin through a community service activity. The method used is a participatory educational approach, including counseling, demonstrations, and simulation practices. The pre-test results indicated that students' knowledge of hypovolemic shock was 81.2%, which significantly increased to 96.15% after the training. Students' skills in recognizing signs and providing first aid also improved significantly. Thus, this program successfully equipped students with the knowledge and skills to handle medical emergencies, while fostering an emergency response culture within the school environment. It is hoped that similar programs can be implemented in other schools to enhance public readiness for medical emergencies.